2006
DOI: 10.1016/j.ymthe.2005.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of SCC-S2 in Experimental Metastasis and Modulation of VEGFR-2, MMP-1, and MMP-9 Expression

Abstract: SCC-S2/GG2-1/NDED (approved gene symbol TNFAIP8) is a transcription factor NF-kappaB-inducible, antiapoptotic, and oncogenic molecule. In this study, we examined the role of SCC-S2 in invasion and experimental metastasis. We demonstrate that expression of SCC-S2 cDNA in MDA-MB 435 human breast cancer cells is associated with enhanced invasion in vitro and increased frequency of pulmonary colonization of tumor cells in athymic mice. Systemic treatment of athymic mice with a cationic liposomal formulation of SCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 44 publications
3
76
0
Order By: Relevance
“…29 It is also a risk factor for non-Hodgkin's lymphoma, and high levels of TNFAIP8 expression are associated with more aggressive forms of epithelial ovarian cancer with poor survival rates 22,30 as well as with non-small cell lung cancer (NSCLC). 31 Furthermore, the overexpression of TNFAIP8 protein in the MDA-MB 435 human breast cancer cell line resulted in increased cell proliferation and cell migration, 17 which was demonstrated to enhance tumorgenicity 32 when injected in athymic mice. In contrast, antisense inhibition in athymic mice resulted in a decreased incidence of pulmonary metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 It is also a risk factor for non-Hodgkin's lymphoma, and high levels of TNFAIP8 expression are associated with more aggressive forms of epithelial ovarian cancer with poor survival rates 22,30 as well as with non-small cell lung cancer (NSCLC). 31 Furthermore, the overexpression of TNFAIP8 protein in the MDA-MB 435 human breast cancer cell line resulted in increased cell proliferation and cell migration, 17 which was demonstrated to enhance tumorgenicity 32 when injected in athymic mice. In contrast, antisense inhibition in athymic mice resulted in a decreased incidence of pulmonary metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…35 Mechanistic studies have shown that decreased TNFAIP8 expression led to concomitant decreases in the levels of vascular endothelial growth factor receptor-2 (VEGFR-2) and matrix metalloprotease (MMP) 1 and 9. 32 In addition, TNFAIP8 has been shown to be directly coupled to Gαi g-proteins; this interaction does not appear to be involved in Gαi3-mediated cAMP inhibition but is involved in Gi-mediated inhibition of cell death, presumably via the Gβγ subunit. 36 TNFAIP8 protein has also been found to associate with activated RAC1-GTP at the cell membrane, 37 and the knockout of this protein resulted in resistance to lethal Listeria monocytogenes infection via decreased RAC1-mediated cell invasion and increased apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Human breast cancer cells transfected with TNFAIP8 increased proliferation, cell migration, and tumor growth rate (Kumar et al, 2004). Knocking down of TNFAIP8 expression in tumor cells reduces their tumorigenicity, suggesting that it may play a role in oncogenesis (Zhang et al, 2006). However, it is not known whether TNFAIP8 takes a part in the progress of PC, and if so, what role it may play.…”
Section: Introductionmentioning
confidence: 99%
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among Abbreviations: BrdU, 5-bromo-2'-deoxyuridine; ChIP-seq, chromatin immunoprecipitation sequencing; DOX, doxorubicin; Gadd45A, growth arrest and DNA damageinducible 45a; H3K4me1, histone H3 mono-methylation on lysine 4; H3K4me3, histone H3 tri-methylation on lysine 4; H3K27ac, histone H3 acetylation on lysine 27; p53RE, p53 response element; PCNA, proliferating cell nuclear antigen; Scri, cells expressing scrambled shRNA; shRNA, short hairpin RNA; TCGA, The Cancer Genome Atlas; TNFAIP8, tumor necrosis factor-α-induced protein 8; TP8i, cells expressing TNFAIP8 shRNA …”
mentioning
confidence: 99%